2014
DOI: 10.1152/ajpgi.00176.2014
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin regulates gastrointestinal motility, inflammation, macromolecular permeability, and mucosal maintenance in mice

Abstract: Enteric neurons express oxytocin (OT); moreover, enteric neurons and enterocytes express developmentally regulated OT receptors (OTRs). Although OT (with secretin) opposes intestinal inflammation, physiological roles played by enteric OT/OTR signaling have not previously been determined. We tested hypotheses that OT/OTR signaling contributes to enteric nervous system (ENS)-related gastrointestinal (GI) physiology. GI functions and OT effects were compared in OTR-knockout (OTRKO) and wild-type (WT) mice. Stool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 64 publications
(79 reference statements)
2
141
0
Order By: Relevance
“…Internal pressure was raised to initiate CMMCs, and spatiotemporal maps of colon diameter as a function of time were constructed. CMMC frequency, velocity, and length of conduction were measured (74,75). See Supplemental Methods for further details.…”
Section: Discussionmentioning
confidence: 99%
“…Internal pressure was raised to initiate CMMCs, and spatiotemporal maps of colon diameter as a function of time were constructed. CMMC frequency, velocity, and length of conduction were measured (74,75). See Supplemental Methods for further details.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the finding that circulating OT may act through central [106] or peripheral OTRs to reduce food intake [105,106] and the observation that peripheral administration can stimulate the release of CNS OT [32], further studies are needed to address the relevance of peripheral OTR signaling in the setting of diet-induced obesity [60,105,106,153,154,160] and whether activation of CNS OT circuits is, in fact, necessary in order to maximize its therapeutic potential when given systemically. While rodent and the small number of nonhuman primate and human studies are promising thus far, OTRs may alter the function of other G protein-coupled receptors, including the beta-2 adrenergic receptor [238].…”
Section: Discussionmentioning
confidence: 99%
“…These data are mixed, however, as peripheral treatment with OT has been reported to have no effect on gastric emptying rate in humans [157] and rats [158] or a stimulatory effect on gastric motility in rabbits, possibly due to species differences [159]. However, systemic OT reduces gastric emptying in both mice [160] and rats [153,154]. Furthermore, these effects are also attenuated by pretreatment with an OTR antagonist, Atosiban [153,154], suggesting that these effects are mediated by OTRs.…”
Section: Potential Role Of Peripheral Otrs In the Nodose Ganglia Or Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it was shown that OTR expression is developmentally regulated during the milk-suckling period in the enteric nervous system and in the epithelial lining, and that toward the end of this period the epithelial OTR translocates to the cryptvillus junctions and to the crypts. In addition, the receptor was found to be expressed at high levels during the suckling period (Welch, Margolis, Li, & Gershon, 2014). It is now established that oxytocin is antiinflammatory in animal models of colitis (Cetinel et al, 2010;Welch et al, 2010) and that gastrointestinal structure, motility, macromolecular permeability, mucosal maintenance, and inflammatory responses are altered in OTR deficient mice (Welch, Margolis et al, 2014).…”
Section: Visceral Oxytocin and Emotional Behaviormentioning
confidence: 99%